Synthesis and Antihypertensive Activity of Some Quinazoline Derivatives - Harsha U. Patel, Ravi S. Patel, Chhaganbhai N. Patel (Journal of Applied Pharmaceutical Science, 2013)
Quinazoline derivatives have been very well known for Antihypertensive activity. Seven new Quinazoline derivatives are synthesized by three steps. Purity of compound is checked by TLC monitoring. All synthesized compounds are confirmed by UV, IR, Mass and H1NMR. All synthesized compound were screened for α1-adrenergic receptor blocking activity. Amongst all synthesized compounds 4a & 4e showed better activity.
Keywords: Quinazolin-4-(3H)-one, &alpha; 1-adrenergic recep